Trade, Jobs, and Inequality - Beaton, Kimberly (IMF Working Papers; Working Paper ;, 2021)
This paper examines the impact of trade on employment, wages, and other outcomes across countries and explores the conditions and policies that help spread the gains from trade more evenly throughout the population. We exploit a large global firm-level dataset to examine the impact of import competition on employment, wages, and firm performance, as well as the firm, industry, and country factors that mitigate any negative impact of an import shock. In contrast to the results of some well-known single-country studies, we find limited adverse impact of import competition. In some countries and industries, import competition actually strengthens employment growth. In addition, import competition tends to improve average wages, investment, and firm profitability. Country characteristics, such as educational attainment, can also improve employment prospects in response to trade shocks. Finally, we find that firms experiencing greater import competition start with higher average wages; thus any relatively slower employment growth in this group of firms could lead to lower inequality.